2022
DOI: 10.15548/jt.v29i2.742
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Student Understanding about Teacher Competency (Personal Competence)

Abstract: This study aims to determine the extent of student understanding of the personality and social competence of teachers. Personality competence is part of teacher competence that must be known by prospective teacher students. This study uses quantitative research methods with a sample of 173 PGSD students in the fourth semester. Based on the results of the study, it was found that 20% of the students did not understand the competence of teachers, especially the personality competencies that prospective teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Based on the results of the study (Amsal et al, 2022), it was found that 20% of the students did not understand the competence of teachers, especially the personality competencies that prospective teachers must possess to become teachers in the future. Characters are defined asmoral excellenceor the morals built in the virtues in turn alone have meaning when it is based on the values that apply in a culture (nation) (Puskur, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of the study (Amsal et al, 2022), it was found that 20% of the students did not understand the competence of teachers, especially the personality competencies that prospective teachers must possess to become teachers in the future. Characters are defined asmoral excellenceor the morals built in the virtues in turn alone have meaning when it is based on the values that apply in a culture (nation) (Puskur, 2010).…”
Section: Introductionmentioning
confidence: 99%